Factors Associated with Caregiver Burden in Patients with Alzheimer's Disease - Kang, Hyo Shin; Myung, Woojae; Kim, Seong Yoon; Lee, Jae-Hong; Han, Seol-Heui; Choi, Seong Hye; Kim, SangYun; Kim, Seonwoo; Kim, Doh Kwan (Psychiatry investigation, 2014)
Caregivers for patients with Alzheimer's disease (AD) suffer from psychological and financial burdens. However, the results of the relationship between burden and cognitive function, performance of activities of daily living, and depressive symptoms have remained inconsistent. Therefore, the aim of this study was to examine which factors are more significant predictors of heightened burden, cognitive impairment or functional decline, besides neuropsychiatric symptoms. A cross-sectional study was conducted in a sample comprised of 1,164 pairs of patients with AD and caregivers from the Clinical Research of Dementia of South Korea study cohorts. The cognitive function of each sub-domain, functional impairments, depressive symptoms, and caregiver burden were assessed using the dementia version of Seoul Neuropsychological Screening Battery (SNSB-D), Barthel Index for Daily Living Activities (ADL), Seoul-Instrumental Activities of Daily Living (S-IADL), the Clinical Dementia Rating Sum of Box (CDR-SB), the Global Deterioration Scale (GDS), the Korean version of the Neuropsychiatric Inventory (K-NPI), and the 15-item Geriatric Depression Scale. We found that higher severity (higher CDR-SB and GDS scores) and more functional impairment (lower ADL and higher S-IADL scores) were significantly associated with higher caregiver burden. In addition, depressive symptoms of patients (higher Geriatric Depression Scale scores) were associated with higher caregiver burden. Therefore, interventions to help maintain activities of daily living in patients with AD may alleviate caregiver burden and improve caregiver well-being.